Comparison of the diagnostic accuracy, sensitivity and specificity of four odontological methods for age evaluation in Italian children at the age threshold of 14 years using ROC curves. (January 2016) - Pinchi, Vilma; Pradella, Francesco; Vitale, Giulia; Rugo, Dario; Nieri, Michele; Norelli, Gian-Aristide
The age threshold of 14 years is relevant in Italy as the minimum age for criminal responsibility. It is of utmost importance to evaluate the diagnostic accuracy of every odontological method for age evaluation considering the sensitivity, or the ability to estimate the true positive cases, and the specificity, or the ability to estimate the true negative cases. The research aims to compare the specificity and sensitivity of four commonly adopted methods of dental age estimation – Demirjian, Haavikko, Willems and Cameriere – in a sample of Italian children aged between 11 and 16 years, with an age threshold of 14 years, using receiver operating characteristic curves and the area under the curve (AUC). In addition, new decision criteria are developed to increase the accuracy of the methods. Among the four odontological methods for age estimation adopted in the research, the Cameriere method showed the highest AUC in both female and male cohorts. The Cameriere method shows a high degree of accuracy at the age threshold of 14 years. To adopt the Cameriere method to estimate the 14-year age threshold more accurately, however, it is suggested – according to the Youden index – that the decision criterion be set at the lower value of 12.928 for females and 13.258 years for males, obtaining a sensitivity of 85% and specificity of 88% in females, and a sensitivity of 77% and specificity of 92% in males. If a specificity level >90% is needed, the cut-off point should be set at 12.959 years (82% sensitivity) for females.